THE USE OF SOCIAL MEDIA AS A ONLINE MEDIUM OF DEAF CHILDREN (STUDY OF FACEBOOK) - Sinta Swastikawara (Universitas Merdeka Malang, 2018)
AbstractThe use of Facebook for deaf children has become a breakthrough in the existence of